'Future Teachers of the Past'- An Analysis of Initial Teacher Training Students and their Preparation to Teach Primary History. Issue 1 (1st November 2012) - Checkley, Paul; Checkley, Claire
Abstract : This paper, developed from original data collected from students on both undergraduate and postgraduate Initial Teacher Training (ITT) courses, from sessions on pedagogical approaches to teaching history in the primary school. With curriculum changes appearing imminent, and the need for students to be able to view the curriculum through a variety of 'subject lenses', we begin to analyse what personal experience students have of being taught 'history', and while on ITT, observing history being taught and their opportunities to teach history. We consider a situational analysis of the student experience and what support has been given to teach history in a Primary School, both as a discrete domain and as part of a cross-curricular approach, on completion of their training. We consider some first thoughts on the effect students' personal view of history teaching may have on the quality of provision in the classroom. We make initial considerations on exploring the 'mindset' of ITT students towards history, as their experience develops.